1992
DOI: 10.1039/c39920000470
|View full text |Cite
|
Sign up to set email alerts
|

Sequence dependent energy transfer from DNA to a simple aromatic chromophore

Abstract: Sequence selective energy transfer f r o m adenine-thymine bases of DNA t o the anthracene chromophore has been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 6 publications
6
62
0
Order By: Relevance
“…30 The high T m value is also consistent with an even greater interaction of the anthracene with the duplex than in related probe systems containing a base site opposite the tether site. 22 note 1 Furthermore, the fact that all the anthracene modified duplexes give uniformly higher T m values than their unmodified counterparts, whether the duplex contains a matching base pair or not, indicates that the anthracene group takes part in effective and broadly similar stabilising interactions with the duplex in each case (vide infra).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…30 The high T m value is also consistent with an even greater interaction of the anthracene with the duplex than in related probe systems containing a base site opposite the tether site. 22 note 1 Furthermore, the fact that all the anthracene modified duplexes give uniformly higher T m values than their unmodified counterparts, whether the duplex contains a matching base pair or not, indicates that the anthracene group takes part in effective and broadly similar stabilising interactions with the duplex in each case (vide infra).…”
supporting
confidence: 56%
“…The increase in fluorescence intensity for the system 5'-CLC/3'-AG can be rationalised by a combination of the hydrophobic environment of the duplex preventing quenching by water and the relatively weak quenching of the proximate adenine, a phenomenon that has been previously observed when anthracene intercalates in AT vs. GC-rich regions of DNA. 30 This quenching effect has in fact been quantified in the case of pyrene intercalators by consideration of the free energy of electron transfer between bases as a result of their different redox potentials. 31 Such an analysis also predicts cytosine to have the greatest thermodynamic driving force for quenching by electron transfer and adenine to have the weakest, which is consistent with what is observed in this study.…”
mentioning
confidence: 99%
“…If small molecule is intercalated into the helix stack, the magnitude of K SV of the bound small molecule should be lower than that of the free one. 15) In contrast, if a small molecule binds to DNA in the groove, the magnitude of K SV of the bound small molecule should be higher than that of the free one. As shown in Fig.…”
Section: Dna-binding Affinity and At Preference Of Tan Iiamentioning
confidence: 99%
“…Corin et al (8) showed that the delayed luminescence spectrum of proflavin is a very useful tool in exploring dynamic interaction between a small molecule and DNA. Kumar et al (9,10) reported that (9-anthrylmethyl) ammonium chloride (AMAC) can bind to DNA with a relatively high affinity. Once binding to DNA, the fluorescence of AMAC will be quenched seriously by DNA base pairs.…”
Section: Introductionmentioning
confidence: 99%